Viability and Economies of Scale in EU Farms - Fürjész, István (Acta Agraria Debreceniensis, 2005)
With this study, the author intends to draw up the main characteristics of the institutional background of the Farm Accountancy Data Network, operated by the European Union. Among the factors that contribute to the formation of the institutional background of the FADN database, special emphasis is laid on the Commission and member state level legal framework, in order to provide potential Hungarian users of the database with authentic and substantial information. Also, much attention is paid to definitional misunderstandings which cause, or might cause the farm business management type utilization of the database to be imperfect. As for this goal, some of the elements of the FADN information structure are investigated in a conventional Hungarian cost structure. In order to facilitate an easier understanding of the database, the different relations of economic size classes are also reviewed in this study. The author of this study is – in the first place – trying to analyze the meaning of Standard Gross Margin, the index used in the FADN structure to categorize farms, by localizing the position of the different cost constituents of SGM in a conventional Hungarian cost matrix. Last, but not least, the author is trying to draw all researcher’s attention on the possibilities, hidden in the FADN database by introducing some analyses from his own field of interest based on FADN information.